Diseño de un bebedero solara a partir de refrigeración por adsorción (2020)
In this project, the design of a solar trough was carried out from the use of adsorption cooling, understanding this method as a way of producing cold without the use of electrical energy to feed the cycle, but gas, using solar energy as the main source thermal. The main objective, then is to design a drinking fountain that makes use exclusively of solar energy for its operation, taking into account the climatic variables and radiation of the city of Buga, as well as seeking the simplicity and functionality of the final design. As a result, a trough is obtained that uses a cooling system according to an estimated amount of water for consumption, with the components required for solar thermal use, obtaining a proposal that makes exclusive use of solar energy for its operation, both for refrigeration and for the activation of electrical elements, such as the submersible pump and temperature and level sensor.